Political economy of cannabis in Thailand - Laohavanich, Mano (Chulalongkorn Medical Journal, 2022)
Cannabis has been classified as category 5 addictive herb. However, the new tread of the world has found it useful resulting a change of policy by the Ministry of Public health in Thailand, i.e., to follow the California Model that allows cannabis to be grown no more than seven in a household. This review article aimed to explore the origin of policy on cannabis of the current government of Thailand, especially under the new Minister of Public Health, its applications, obstacles and plausible solutions and the policy suggestion for deregulation of cannabis. Literature reviews were conducted on history of cannabis, ingredients, risks and benefits of cannabis as well as in-depth interviews of three stakeholders in the field of cannabis pharmacy, naturopathy and national policy making in the Ministry of Public Health. Cannabis is a useful pharmaceutical plant, easily grown in Thailand, and deserved to be deregulated following the trend in the West. However, in Thailand it should not be used freely but controlled and regulated. It will take decades for cannabis extracts to be used in conventional Medicine, but in Thai Traditional Medicine the formula that use cannabis have been known in Thailand for no less than 300 years at least since the reign of King Narai of Ayutthaya. Therefore, it should be encouraged and will be of great benefit to the economy. Cannabis should definitely be banned from recreation uses, and the government should encourage more research and development of cannabis to be used for medical purposes, both in the Thai Traditional Medicine and Conventional Medicine. The former has an advantage that in the production of cannabis-based traditional medication does not require trials in animal and human models; the pharmaceutical company can directly jump to the production of the medication right away as it has been used in Thai society for hundreds of years. The latter will need more time and financial supports from investors and international community as mandated by the protocol for pharmaceutical industry. Nevertheless, for safety of the consumer quality of cannabis cultivation, storing and production have to be controlled by the government.